Remediation of metal-contaminated marine sediments using active capping with limestone, steel slag, and activated carbon: a laboratory experiment - Park, Seong Jik; Kang, Ku; Lee, Chang Gu; Choi, Jae Woo (Environmental Technology (United Kingdom), 2019)
The objectives of this study are to assess the effectiveness of limestone (LS), steel slag (SS), and activated carbon (AC) as capping materials to sequester trace metals including As, Cd, Cr, Cu, Ni, Pb, and Zn in heavily contaminated marine sediments and to minimize the release of these metals into the water column. A flat flow tank was filled with 10 mm of capping material, contaminated sediments, and seawater, and the metal concentrations were monitored over 32 d. After completion of the flow tank experiments, the sediments below the capping material were sampled and were sequentially extracted. SS effectively reduced the As, Cr, Cu, Ni, Pb, and particularly Cd elution from the contaminated sediments to the overlying seawater. Adsorption and surface precipitation were the key mechanisms for interrupting the release of cationic trace metals by SS. LS was appropriate for interrupting the release of only Cu and Pb with high hydrolysis reaction constants. AC capping could interrupt the release of Cr, Cu, Ni, and particularly Zn from the sediments by binding with the metals via electrostatic interaction. The results obtained from the sequential extraction revealed that LS capping is appropriate for stabilizing Zn, whereas AC is appropriate for Cd and Pb. LS, SS, and AC can be applied effectively for remediation of sediments contaminated by trace metals because it interrupts their release and stabilizes the trace metals in the sediments.
Keywords: Active capping; Contaminated marine sediments; Contaminated sediment; Laboratory experiments; Sequential extraction; Steel slag; Surface precipitation; Trace metal; Calcium Carbonate; Charcoal; Environmental Monitoring; Geologic Sediments; Metals, Heavy; Steel; Water Pollutants, Chemical; Activated carbon; active capping; limestone; steel slag; trace metals